Environmental perception and control of gastrointestinal immunity by the enteric nervous system. Issue 11 (November 2022) - Schneider, Kai Markus; Kim, Jihee; Bahnsen, Klaas; Heuckeroth, Robert O.; Thaiss, Christoph A.
Abstract : The enteric nervous system (ENS) forms a versatile sensory system along the gastrointestinal tract that interacts with most cell types in the bowel. Herein, we portray host–environment interactions at the intestinal mucosal surface through the lens of the enteric nervous system. We describe local cellular interactions as well as long-range circuits between the enteric, central, and peripheral nervous systems. Additionally, we discuss recently discovered mechanisms by which enteric neurons and glia respond to biotic and abiotic environmental changes and how they regulate intestinal immunity and inflammation. The enteric nervous system emerges as an integrative sensory system with manifold immunoregulatory functions under both homeostatic and pathophysiological conditions. Highlights: The enteric nervous system (ENS) is in its organization, structure, and function more similar to the central nervous system (CNS) than to other parts of the peripheral nervous system (PNS). Recent groundbreaking advances in single-cell genomics and imaging technologies allow unprecedented insights into different functional neuron and glia populations. Enteric neurons closely interact with glia cells and virtually all intestinal cell types. These interactions position the ENS in the center of manifold regulatory circuits for immunity and metabolism under homeostatic and pathophysiological conditions. Together, the ENS, enterocytes, and immune cells form one of the body's most advanced sensory systems that is strategically located in the gastrointestinal wall to trigger orchestrated responses to environmental changes.